Daily wellness behaviors in college students across a school year. Issue 6 (24th August 2022) - Copeland, William E.; Bai, Yang; Adams, Zoe; Lerner, Matthew; King, Jessica A; Rettew, Jeff; Hudziak, Jim
Abstract: Objective: To establish the prevalence of mood and wellness behaviors in college students across a school year. Methods: 1, 554 college students (69.4% female; average age 18.8 years) were followed with daily surveys on wellness behaviors for the school year. 1, 207 participants completed at least 50% of daily surveys on mood, exercise, sleep, nutrition, mindfulness practice and singing/playing musical instrument. Results: Over 88.7% of college students reported at least one wellness behavior each day with 17.7% reporting 4 or more. Each of the wellness behaviors, however, displayed distinct prevalence patterns, varied significantly across the school year, and often across a given school week. Almost every individual wellness behavior was associated with a positive mood, and the cumulative number of daily wellness behaviors was a strongly associated with mood state. Conclusions: Daily wellness behaviors are collectively common, vary significantly within individuals, and are strongly associated with positive mood, both individual and cumulatively.